What is the role of helminth therapy for inflammatory bowel disease?. Issue 5 (May 2017) - Obholz, Joshua J.; Persons, Robert K.
Abstract : EVIDENCE‐BASED ANSWER : Evidence is insufficient to recommend helminth therapy for inflammatory bowel disease (IBD) (SOR: B, systematic review of 2 small RCTs and a single RCT).